2003
DOI: 10.1093/ageing/32.3.321
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of malnutrition in older people during and after hospitalisation: results from a randomised controlled clinical trial

Abstract: use of daily oral supplementation during and after hospitalisation maintains body weight and increases Mini Nutritional Assessment score in patients at risk of undernutrition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
76
0
5

Year Published

2005
2005
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(84 citation statements)
references
References 25 publications
3
76
0
5
Order By: Relevance
“…That older patients in hospital are being at greater risk for undernutrition than those who just had been admitted from home is in line with the results from a study among young and older patients by Rasmussen et al (2004), who found a statistically significant relationship between lengths of stay and weight loss. This can be compared to Gazzotti et al (2003), who showed statistically significant weight loss during the hospital stay in older patients not receiving oral supplementation. Furthermore, Margetts et al (2003) have shown in a study that older male patients in hospital were more likely to be at medium or high risk for undernutrition.…”
Section: Discussionmentioning
confidence: 93%
“…That older patients in hospital are being at greater risk for undernutrition than those who just had been admitted from home is in line with the results from a study among young and older patients by Rasmussen et al (2004), who found a statistically significant relationship between lengths of stay and weight loss. This can be compared to Gazzotti et al (2003), who showed statistically significant weight loss during the hospital stay in older patients not receiving oral supplementation. Furthermore, Margetts et al (2003) have shown in a study that older male patients in hospital were more likely to be at medium or high risk for undernutrition.…”
Section: Discussionmentioning
confidence: 93%
“…However, there have been some other studies, often small in size, in which the nutritional status of elderly patients in Belgian hospitals was investigated. [20][21][22][23][24] These studies focused, for example, on the prevention of malnutrition, a nutritional care program, a minimum geriatric screening tool to detect geriatric problems including nutrition, and the use of the MNA. In two of these studies the prevalence of malnutrition was explored.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have documented hospitalisation as an important risk factor for UWL (12,33,34), a finding that may indicate a special nutrition-directed home nurse visit after discharge. We noticed that the meals-on-wheels activity was the same regardless of weight loss, so the simple addition of meals on wheels is not enough to ensure that lost weight is regained.…”
Section: Identifying Signs Of An Early Stage Of Undernutrition In a Hmentioning
confidence: 99%